(untitled) (ModaPalavra e-periódico, 2025)
As the fashion industry is a sector in constant expansion that is responsible for generating jobs and driving the economy worldwide, it is imperative that it ensures the protection of the lives of its creations before the competent body. As it is one of these protective models, industrial design appears to be little used by this segment, especially in the Afro-Brazilian fashion that supports this work. Therefore, technological prospecting was carried out in the INPI databases, as well as a bibliographic survey on the topic, in order to analyze and quantify the registration requests made by entrepreneurs working in this field. Through this prospecting, it was found that there were very few registration requests related to Afro-Brazilian fashion, revealing that many entrepreneurs in the sector start with little financial structure and knowledge about topics important to the business, which ends up leaving their inventions without debt protection. . Furthermore, there is a gap in the specific literature on the topic that can guide Afro-Brazilian fashion professionals to protect their products and inventions. Thus, there is a need to finance the issue of intellectual property for these entrepreneurs and guarantee the promotion of enabling and educational public policies and thus insert businesses into the market in a safe way and with security structures.